Mining of the added resistance of ships advancing in waves - Lim, Desmond Wei Sheng (Nanyang Technological University, 2022)
Added wave resistance is defined as the difference between the time averages of the longitudinal force experienced by a ship in rough waters as compared to the force in calm waters, it is one of the parameters being closely scrutinized in recent years by the shipping industry. This project aims to predict the added wave resistance of common shipping vessels by creating an intuitive backpropagation artificial neural network model on Python using known physical parameters of those vessels while limiting the usage of preexisting libraries.